1, 3-Dipolar cycloaddition reactions of enaminones and azides: Synthesis of 4-acyl-1, 2, 3-triazoles and mechanistic studies. (13th August 2022) - Gaspar, Francisco V.; Azevedo, Marcelo F.M.F.; Carneiro, Leonardo S.A.; Ribeiro, Samuel B.; Esteves, Pierre M.; Buarque, Camilla D.
Abstract: 4-acyl-1, 2, 3-triazoles are an important and versatile chemical scaffold widely applied in medicinal chemists due to their interesting pharmacological properties. Acknowledging the constant need for a greener, simple and scalable methodology in medicinal chemistry, herein we report the synthesis of new 4-acyl-1, 2, 3-triazoles through the metal-free and solvent-free cycloaddition reactions between enaminones and aryl azides, obtaining yields of 41–77%. Based on experimental Hammett correlation and theoretical Quantum calculations data a reaction mechanism for 3-dipolar cycloadditions synthesis of 4-acyl-1, 2, 3-triazoles was proposed. Graphical abstract: Image 1 Highlights: New 4-acyl-1, 2, 3-triazoles were synthesized through 1, 3-dipolar cycloaddition reaction. Enaminones and aryl-azides were used as substrates for the metal and solvent-free methodology. The mechanism of the reaction was experimentally investigated by the LFER. The mechanism of the reaction was computationally investigated by DFT and LFER.